Sistem Penunjang Keputusan dalam Optimalisasi Pemberian Insentif terhadap Pemasok Menggunakan Metode TOPSIS - Vicky Setia Gunawan (SAFE-Network, 2021)
Generally, every company must have an assessment of the supplier of materials in order to maintain the quality of their production. When a supplier gets a good rating, the company usually gives awards such as incentives to the supplier in the hope of increasing motivation, professionalism and good relations with the company. The determination of incentives is currently only based on analysis of existing data records manually, which may lead to errors. From previous observations, a decision support system was created in the optimization of incentives. This study aims to optimize the results of decisions in providing incentives to suppliers. The method used is Technique for Others Preference by Similarity to Ideal Solution (TOPSIS). This method can determine which suppliers are entitled to incentives. The data that is processed in this research comes from PT. Prima Beton Cakrawala. Price, Quality, Delivery, Service and Offer are the assessment criteria for determining incentive recipients. The results of the TOPSIS calculation process can find a more accurate alternative choice decision, because the alternative assessment is in accordance with the specified criteria. Based on the value of the criteria weight for the selection of incentive recipients for each alternative. The results of this study recommend A3 suppliers with a preference value of 0.646 as raw material suppliers who are entitled to receive incentives. Comparisons made between manual calculations and the system built get almost the same results. So that the level of accuracy is 95% accurate enough, so that it can produce factual decision data in order to assist companies in determining incentive recipients so as to increase the motivation of suppliers in providing services. So that it is expected that the leadership can use it as a reference for optimizing decisions on providing incentives.